DESAIN DAN PENGEMBANGAN INTERNET OF THINGS SEBAGAI MONITORING KETERSEDIAAN AIR BERSIH BERBASIS NodeMCU ESP8266 (STUDI KASUS: KP.BANTARWARU KECAMATAN MUNCANG KABUPATEN LEBAK) - Dede Lukman Lukman Hakim; Agung Budi Susanto; Sudarno Wiharjo (JUPIK : Jurnal Penelitian Ilmu komputer, 2023)
One of the essential human needs that must be fulfilled is clean water, and using reservoirs is one of the alternative to collect clean water that from mountains. The process of distributing water from the mountain to the reservoirs sometimes encounter issues that chough up the water from reaching the reservoirs. These issues can be caused by natural phenomena, such as a decrease in the quality of the water source, or other factors like leaks or pipes disconnection. Periodic monitoring of the water source's condition is necessary to identify the causes of these problems. One of the method for monitoring the condition of mountain water sources is by utilizing the concept of the Internet of Things (IoT). This allows remote monitoring using water flow sensor to collect data on water flow and ultrasonic sensor to measure water levels. The data is then transmitted via the internet using the NodeMCU 8266 microcontroller. The research stages include identifying needs, needs and design analysis, variable value analysis, program design, program development, and testing. The testing involves functional and performance tests to ensure the system operates effectively, enabling personnel to identify the causes of issues that cough up water from reaching the reservoirs. The result of this research is a device that can monitor the availability of water in the reservoirs and easily track the quantity of clean water from the water source through a website.